Optical fibre-based refractive index measurement sensor. (3rd February 2023) - Terdale, Jayprabha Vishal; Ghosh, Amrit
Optical devices are increasingly widely used in surveillance, particularly in the food, beverage, and healthcare sectors. A precise refractive index profile is required to support maximum light intensity on the fibre material. But unpolished optical fibre has a difficult RI profile. By changing the solution's concentration, it allows precise RI measurement. We present an intensity modulated fibre optic refractive index measurement using macro-bending and side polishing. RI conditions and the dipping solution concentration in the detecting region are more sensitive to probes with a polished surface (sucrose, glycerin, and ethanol). With RI 1.34-1.42, the POF performance sensing capability increases. This allows for physical variations in intensity at visible wavelengths at cheap cost and compact size.